Methodology for the assessment of distributed propulsion configurations with boundary layer ingestion using the discretized miller approach - Valencia, Esteban; Liu, Chengyuan; Nalianda, Devaiah; Panagiotis, Laskaridis; Gray, Iain; Singh, Riti (Praise Worthy Prize, 2017)
The growing global environmental awareness has motivated the search for more fuel-efficient aircraft propulsion systems. In this context, a configuration based on distributed propulsion with Boundary Layer Ingestion (BLI) has been found to present potential performance benefits. The concept has been documented and explored extensively during the last few years and various aerodynamic integration issues, such as: high levels of distortion and low intake pressure recovery; have been identified as factors that may be detrimental in realizing the technology full potential. Parametric and parallel compressor (PC) approaches have been used to assess the effect of these aerodynamic issues on propulsors fan performance. However, in the context of BLI, these tools are unable to assess the effects of combined radial and circumferential distortion that are present. In order to assess the combined distortion patterns and the effects of distortion at component and system levels, this study uses a novel method based on semi-empirical correlations denominated the Discretized Miller (DM) approach. This method was developed for BLI systems previously by the author, and it is now incorporated into the propulsor performance method to assess the effects of the combined radial and circumferential distortion patterns. The performance analysis, undertaken at a component and system level, aims to assess several propulsion architectures, using Thrust Specific Fuel Consumption (TSFC) as figure of merit. To define the suitability of the distributed propulsor array in this study, an airframe layout based on the N3-X aircraft concept and High Temperature Superconducting (HTS) electric motor capabilities were assumed. The key contribution of this study is to enable the introduction of the concept of thrust split between energy source and propulsion system in the system analysis, and thereby, allows the assessment of its effects on different propulsion system layouts, while considering the BLI induced distortion. The results obtained with this alternative performance method showed that BLI reduces the fan efficiency of a conventional fan by approximately 2%, whilst corroborating the TSFC trends observed in previous studies. The study also indicates that when sizing effects of propulsors and core-engines were neglected, a propulsion system configuration with 75% thrust split was found optimum.
Reproduced with permission from Praise Worthy Prize (info@praiseworthyprize.it) 23.4.2018
Keywords: Boundary Layer Ingestion; Distributed Propulsion; Thrust Split; Propulsion Configurations